Service quality and perceived value towards revisit intention of EI’s coffee in Padang by customer satisfaction as mediating variable - Rivo Dwi Harman; Arief Maulana (Universitas Negeri Padang, 2021)
This research aims to analyze determine the influence of service quality and perceived value on the intention to revisit padang el's coffee with customer satisfaction as the mediating variable. The sample in this study were 100 customers at El's Coffee Padang City. Data were processed using Smart PLS 3.0. The results obtained from this study are: (1) There is a direct and significant and positive influence between service quality and the perceived value of El`s Coffee Padang. (2) There is a direct and significant and positive influence between service quality and customer satisfaction at El`s Coffee Padang. (3) There is a direct and significant and positive influence between perceived value and customer satisfaction at El`s Coffee Padang. (4) There is a direct and significant and positive influence between customer satisfaction and the intention to revisit El`s Coffee Padang.